Antifungal Susceptibility Pattern of Candida Isolates Causing Vulvovaginitis in Reproductive Age Women - Shrestha, Pabitra; Pokharel, Sunil Mani; Shrestha, Anima (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The study was designed to isolate and identify Candida species from high vaginal swab, and to determine the antifungal susceptibility pattern of Candida spp. among women of reproductive age group i.e. 15- 50 years old. Methods: High vaginal swabs were processed to isolate Candida species and identified by Gram’s stain, germ tube formation test, carbohydrate (glucose, sucrose, maltose, lactose) fermentation tests and antifungal susceptibility test were performed as recommended by Clinical Laboratory Standard Institute. Results: Out of total 261 samples, 42.1% (110/261) were found to be culture positive for Candida spp. Candida albicans was the most common (56.4%) and among non-albicans, predominate species was C. krusei (19.1%) isolated from high vaginal swab specimens All the isolates of Candida species were sensitive to Nystatin and Miconazole and resistant to Itraconazole. Fluconazole, Itraconazole and Clotrimazole are widely used drug against vaginal candidiasis but showed high resistance which leads to treatment failure. Conclusion: This study on the infection rate of Candida and its antifungal susceptibility pattern may help in the choice of appropriate therapy in the clinical setting.